EFFECT DEGRADABLE PROTEIN LEVEL G/MJ METABOLIZABLE ENERGY THROUGH DIFFERENT STAGES OF LACTATION ON MILK YIELD AND COMPOSITION OF AWASSI EWES - Almallah, O. D. M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study investigated the effect of feeding two levels of rumen degradable protein in the rations during different stages of lactation on milk yield and components , twenty four cross breed Awassi ewes (Turkish Awassi × Iraqi Awassi) were used with their single lambs after birth aged 3-5 years, ewes were divided into two groups with average body weights 66.00 ± 2.32 kg and 67.10 ± 2.62 kg respectively, first group was control fed adequate level of degradable protein (10 g / Mj metabolizable energy) and second group fed high level of degradable protein (12.5 g / Mj metablizable energy) , Lactation period had been divided into three stages (early, 1-50 day ), ( mid , 51-100 day) and (late , 101-150 day), ewes were fed twice daily with restricted amount 2 kg in the early and mid and 1.5 kg in late lactation . Results showed that feeding adequate level of rumen degradable protein led to significant ( P< 0.05) increase in milk yield 785 g/day and lactose 5.81% as compared with high level 619 g/day and 5.58% respectively, also milk yield decreased ( P< 0.05) while milk fat increased ( P< 0.05) with advance milk period. Blood parameters were not affected significantly by feeding degradable protein while serum glucose, total protein and albumin decreased (P< 0.05) at late stage of milk production. Best results of interaction for rumen degradable protein and milk stages in milk yield and components yield were noted with feeding adequate level of rumen degradable protein in the early lactation.